Effect of co-culturing of half-destroyed and intact 4-cell mouse embryos in varying ratios on subsequent in vitro development - Sanmee U. (2014)
We studied the co-culturing effect of intact and half-destroyed 4-cell mouse embryos on blastocyst formation rate and cell counts. A laser beam was used to produce a hole and destroy an adjacent blastomere in two opposite areas of the zona in the experimental group (n = 342), and to open two opposite zonal holes in the controls (n = 318). Control and half-destroyed embryos were cultured together in varying ratios of 10:0, 7:3, 5:5, 3:7, and 0:10 (group 1-5, respectively) for 48 h in 10 μl drops of cleavage medium. They were then separated and cultured in blastocyst medium for 24 h. The results showed that half-destroyed embryos had no effect on the blastulation rates of controls (97-100%, P = 0.28). Neither was there a difference in the number of ICM (27.3 ± 6.7, 29.4 ± 9.9, 27.7 ± 9.3, 26.5 ± 6.4, in group 1-4, respectively; P = 0.491), TE (47.7 ± 18.6, 52.3 ± 13.9, 48.4 ± 19.2, 57.3 ± 12.9, in group 1-4, respectively; P = 0.101), nor total cells (75.0 ± 19.5, 81.3 ± 17.1, 76.1 ± 19.6, 83.7 ± 16.2, in group 1-4, respectively; P = 0.188) in the resulting blastocysts. However, among half-destroyed embryos, cleavage arrest decreased (58.3%, 39.6%, 17.9%, and 8.3%, in group 5 to 2, respectively; P < 0.001) and blastocyst development increased (38.3%, 58.2%, 72.6%, and 88.9%, in group 5 to 2, respectively; P < 0.001) following co-culturing with intact controls. These embryos had a higher number of ICM cells (P = 0.035), but no significant changes in TE (P = 0.262) and total cell counts (P = 0.065). The findings indicate that the co-culturing of half-destroyed with intact embryos increased the blastulation rate of the first but had no effect on the latter. © 2011 Elsevier Inc.